Amino acid analysis of type 3 chondrites Colony, Ornans, Chainpur and Bishunpur - Chan,HS; Martins,Z; Sephton,MA (Meteoritics & Planetary Science, 2012)
The CO3s Colony and Ornans and LL3s Chainpur and Bishunpur were analyzed for the first time for amino acids using gas chromatography–mass spectrometry (GC-MS). Type 3 chondrites have relatively unaltered metamorphic and petrological histories. Chainpur was the most amino acid rich of the four type 3 chondrites with a total amino acid abundance of 3330 parts per billion (ppb). The other type 3 chondrites had total amino acid abundances that ranged from 660 to 1110 ppb. A d/l ratio of <0.7 for all proteic amino acids suggests at least some amino acid terrestrial contamination. However, a small fraction of indigenous extraterrestrial amino acids cannot be excluded because of the presence of the nonprotein amino acid α-aminoisobutyric acid (α-AIB), and unusually high relative abundances (to glycine) of β-alanine and γ-ABA. The comparisons between the free and total amino acid contents of the samples also indicate a low free/total amino acid ratio (ranging from about 1:4 in CO chondrites to about 1:50 in Chainpur), which indicate that amino acids are present mainly in the bound form and were made detectable after acid hydrolysis.